Design And Construction Of Information Systems For Institutional Legal Aid Consultation Services Web-Based Legal Aidwith The Waterfall Method (Case Study At Lbh Hamka Garut) - Ramdhani Hidayat; Rahayu, Dinar; Fikri Alamsyah, Fahmi (RISTEC : Research in Information Systems and Technology, 2024)
Abstract: The very rapid development of information technology is something that cannot be avoided in a very modern era like today. The role of technology is very large in human activities, for example legal aspects, health aspects and other aspects. The development of information systems is able to facilitate and help human work so that they can complete work effectively and efficiently. In this research, researchers used the waterfall method, where the waterfall method is something that describes a systematic and sequential (step by step) approach to software development. Researchers use UML modeling to model the process of the system to be built. The implementation of requirements for this system is taken based on the results of previous requirements analysis which includes several requirements including software requirements and hardware requirements. Apart from implementing these two requirements, the implementation process further includes the system implementation process by implementing code using the PHP programming language, database using MySQL and local server using XAMPP. It is hoped that this service information system will make the legal consultation service process at the institution more efficient. Keywords: Keywords: Consulting information system, Waterfall Method, UML